Sleep and incubation: using problem reactivation during sleep to study forgetting fixation and unconscious processing during sleep incubation. Issue 6 (3rd October 2021) - Sanders, Kristin E. G.; Beeman, Mark
ABSTRACT: When people are stuck on a problem, they sometimes benefit from an incubation period—a break from working on the problem. Anecdotes and empirical evidence suggest that sleeping during incubation is useful, but the mechanisms remain poorly understood. We examined how targeted memory reactivation during sleep, which boosts next-day solving, relates to forgetting fixation, a well-supported explanation of awake incubation. In evening sessions, participants attempted puzzles, while a unique sound cue played during each puzzle. Half the time, puzzles included fixating information reinforcing an incorrect representation. Later, during deep sleep, sounds associated with half of participants' previously unsolved puzzles were presented. The sounds should strengthen puzzle memories and reduce forgetting of the fixating information. In morning solving, overnight cueing reliably interacted with fixating information: participants solved numerically more cued than uncued puzzles, but only when puzzles included fixating information. These results suggest that additional processing occurred beyond simple fixation forgetting.